2021
DOI: 10.1111/and.14123
|View full text |Cite
|
Sign up to set email alerts
|

Is addition or removal of seminal plasma able to compensate for the dilution effect of buffalo semen?

Abstract: Summary The present study aimed to compensate dilution effect using additional seminal plasma (SP) in conventional (80 million (M) spermatozoa/ml) dose and low spermatozoa/dose (8M spermatozoa/ml). We also attempted to confirm whether removal of SP before the extension of ejaculates affects post‐thaw sperm quality of buffalo semen. For this, semen ejaculates (N = 15) were divided into four groups: control (CON), removal of SP by centrifugation (NSP), resuspension of the centrifuged semen pellet into SP (CEN) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…Superoxide anion is the principal ROS produced by mitochondria. The MitoSOX‐based assay has been used to identify sperm population that generated high superoxide after the freeze–thaw process due to the ability of MitoSOX to permeate live cells where it selectively targets mitochondria (Arjun et al, 2021; Dalal, Chandolia, Jan, et al, 2020; Patil et al, 2020). It is quickly oxidized by superoxide but not by other ROS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Superoxide anion is the principal ROS produced by mitochondria. The MitoSOX‐based assay has been used to identify sperm population that generated high superoxide after the freeze–thaw process due to the ability of MitoSOX to permeate live cells where it selectively targets mitochondria (Arjun et al, 2021; Dalal, Chandolia, Jan, et al, 2020; Patil et al, 2020). It is quickly oxidized by superoxide but not by other ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The JC‐1 dye was used to estimate MMP as performed by Arjun et al (2021). The working solution of JC‐1 (1.5 mM in DMSO) was mixed with a semen sample to make a final concentration of 2 μM of JC‐1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However the proportions of moribund spermatozoa, dead spermatozoa, live acrosome reacted (LAR) spermatozoa, dead acrosome intact (DAI) spermatozoa and capacitated spermatozoa increased ( p < 0.05) when semen was diluted from 20 to 5 M. We found that sperm protamine deficiency and sperm lipid peroxidation were not affected by dilution. The semen dilution significantly affected the proportion of HOS responsive spermatozoa when buffalo semen was diluted to 2 million spermatozoa (Arjun et al, 2021). In mammals, the dynamics of sperm chromatin are greatly determined by protamination of sperm DNA (Talbert & Henikoff, 2010; Ward, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…and rat [24] kidney after cold preservation. MitoQ could cross the rat blood-testis barrier and protect against rodent testicular injury by promoting the expression of mitochondrial dynamics proteins [44], activating antioxidant enzymes, and inhibiting apoptosis indicators [19] .The addition of MitoQ at various nanomolar concentrations in extender lowered the production of ROS and lipid peroxidation and improved sperm quality in frozen-thawed semen of catfish [13], human [21], buffalo [6], and rooster [25]. In buffalo semen, MitoQ indicated more cryotolerance than Resveratrol as a cytosolic antioxidant [38].…”
Section: Introductionmentioning
confidence: 99%